Identifying the Epileptogenic Zone With the Relative Strength of High-Frequency Oscillation: A Stereoelectroencephalography Study - Qi, Lei; Fan, Xing; Tao, Xiaorong; Chai, Qi; Zhang, Kai; Meng, Fangang; Hu, Wenhan; Sang, Lin; Yang, Xiaoli; Qiao, Hui (Frontiers in Human Neuroscience, 2020)
Background High frequency oscillation (HFO) represents a promising biomarker of epileptogenicity. However, the significant inter-individual differences among patients limit its application in clinical practice. Here, we applied and evaluated an individualized, frequency-based approach of HFO analysis in Stereo-electroencephalography (SEEG) data for localizing the epileptogenic zones (EZ). Methods Clinical and SEEG data of 19 patients with drug-resistant focal epilepsy were retrospectively analyzed. The individualized spectral power of all signals recorded by electrode array, i.e., the relative strength of HFO, was computed with a wavelet method for each patient. Subsequently, the clinical value of the relative strength of HFO for identifying the EZ was evaluated. Results Focal increase of the relative strength of HFO in SEEG recordings were identified in all 19 patients. HFOs identified inside the clinical identified seizure onset zones had more spectral power than those identified outside (p < 0.001), and HFOs in 250-500 Hz band (fast ripples) seemed to be more specific in identifying the EZ than in those in 80-250 Hz band (ripples) (p < 0.01). The resection of brain regions generating HFOs resulted in a favorable seizure outcome in 17 patients (17/19; 89.5%), while in the rest 2 patients with a poor outcome, the brain regions generating HFOs were not removed completely. Conclusion The relative strength of HFO, especially fast ripples, is a promising effective biomarker for identifying the EZ, and can lead to a favorable seizure outcome if used to guide epilepsy surgery.